Eksperimen Mengelola Sampah untuk Meningkatkan Pengetahun, Sikap, dan Perilaku Masyarakat Pada Kompleks Perumahan Kemiringan Tanah 5 Sampai 10 Derajat di Kabupaten Mamasa - Andi Yusdy Dwiasta R; Bakhrani A Rauf; Husain Syam; Faizal Amir (Seminar Nasional LP2M UNM, 2022)
Abstract. The objectives of the study were: (1) to determine the knowledge, attitudes, and behavior of managing the waste of the community who inhabit the residential houses with a slope of 5 to 10 degrees before and after the experiment in Mamasa Regency, (2) to determine the effect of the experiment on increasing knowledge, attitudes, and community behavior in managing waste who inhabiting houses with a slope of 5 to 10 degrees in Mamasa Regency. This research is classified as quantitative research and the approach used is experimental research. The research location is in Mamasa Regency. The sample area was chosen intentionally (purposive sampling), namely Mambuliling Village. Respondents as many as 25 families were selected by purposive sampling method. The experimental design used was One Group Pretest-posttest Desigen (Borg and Gall, 2008). The research variables are: (1) knowledge about waste, (2) attitude to manage waste, and (3) behavior in managing waste before and after the experiment. The data analysis techniques used are: (1) descriptive statistical analysis, and (2) inferential statistical analysis. The analytical model used is the correlation t test.The results showed that: (1) the knowledge, attitudes, and behavior of the community in managing the waste who inhabited the residential houses with a slope of 5 to 10 degrees in Mamasa Regency before the experiment was classified as low and after the experiment was classified as high, (2) Experiments had an effect on increasing knowledge, attitudes, and behavior of the community in managing waste who inhabited the residential houses with a slope of 5 to 10 degrees in Mamasa Regency.  Keywords: Waste, Knowledge, Attitude, and Behavior.